Applying the quick exposure check in the workstation design process, physical and virtual prototype assessment. - Ipaki, Bahram; Molenbroek, Johan F.M.; Merrikhpour, Zahra; Faregh, Seyed Ali (Work, 2023)
BACKGROUND: The Quick Exposure Check (QEC) assesses four major body parts and engages users in assessing some physical interactions relevant to design in task analysis. OBJECTIVE: In this paper, we investigated the application of QEC as the ergonomic intervention to detect pre-production ergonomic design faults in the apple sorting machine by applying physical and virtual prototyping for three different tasks analysis divided into two phases (Task 1: Apple harvesting and preparation for sorting; Task 2: Sorting control and separation of waste fruits; Task 3: Transfer of separated apples). METHOD: First, the QEC questionnaire was administered while Iranian participants interacted with the machine to detect abnormal posture. Second, we redesigned a concept of the machine and assessed it with QEC by a focus group. RESULTS: Before design, the high pressure in Task 1 is on the back (dynamic), shoulder/arm, and very high pressure in Task 2, and in Task 3 on the back (static), arm/shoulder/neck, making an uncomfortable situation for posture. After redesign, we observed decreased pressures on the back/shoulder/arm in Task 1 from high to medium, in Task 3 from very high to low, and also in Task 2, this was detectable decreasing from very high pressures on the back/shoulder/arm and the high pressures on the neck to medium. CONCLUSION: Prototyping with QEC demonstrated that accurate redesigning of the machine with concentration on shifting from static tasks to dynamic or conversely, and ease of access by adjusting dimensions according to anthropometry and auxiliary products, could reduce musculoskeletal disorders.